PENGEMBANGAN PROGRAM PEMBINAAN LITERASI MEDIA BAGI SISWA TUNARUNGU - Rina Dwi Kurniawati; Asri Wijiastuti; nFn Yuliyati (Balai Besar Guru Penggerak Jawa Timur, 2020)
This study aims to produce a media literacy development program for deaf students in schools. The deaferation behavior of deaf students at school so far has not been able to show their ability to use media as a tool for literacy, learning resources, and there is no follow up after the activity takes place. Media literacy is needed by deaf students because various information can be obtained from technology media. Development of media literacy is done with the aim that students with hearing impairment: (1) are able to utilize the media for positive activities and use media properly and appropriately, and (2) have provision in lifelong learning. The method used is Research & Development (R&D) with 10 stages. Instruments to determine the level of media literacy ability of deaf students and their activeness using daily reading journals are interviews, observation, and documentation. The results showed that media literacy coaching could increase student awareness of using media as a means of literacy. The results of the material validation state that the product developed is